1998
DOI: 10.1002/(sici)1097-4628(19980425)68:4<535::aid-app4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of EPDM films

Abstract: A series of ethylene-propylene-2-ethylidenebicyclo[2.2.1]hept-5-ene terpolymers have been prepared using the VOCl 3 /Al 2 Et 3 Cl 3 catalyst under various initial Al/V ratios and diene concentrations. The V/C and Al/V ratios in EPDM films were determined by Rutherford backscattering spectrometry. The concentration of incorporated vanadium increases with the increase of the iodine number, i.e., with the number of double bonds in the polymer. However, the concentration of incorporated V in the terpolymers remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…34 Besides, it was already shown that only 18% of the V in the reaction milieu is present as active species. 35 In a previous study, 25 we observed that the Al/V molar ratio incorporated in polymers remains roughly constant (between 6.0 and 7.5) independent of the initial Al/V molar ratio in the solution, which was attributed to the percentage of active V(III) species. Then it seems that the amount of Al/V, which remains in the polymer, corresponds to the metal ratio necessary to generate the active species.…”
Section: Figurementioning
confidence: 79%
See 3 more Smart Citations
“…34 Besides, it was already shown that only 18% of the V in the reaction milieu is present as active species. 35 In a previous study, 25 we observed that the Al/V molar ratio incorporated in polymers remains roughly constant (between 6.0 and 7.5) independent of the initial Al/V molar ratio in the solution, which was attributed to the percentage of active V(III) species. Then it seems that the amount of Al/V, which remains in the polymer, corresponds to the metal ratio necessary to generate the active species.…”
Section: Figurementioning
confidence: 79%
“…We have observed previously that the V content increases with the diene concentration and this might be an effect of activity loss by the increasing amount of diene. 25 Together with this fact, V atoms might interact somehow with unsaturations present in those terpolymers. We attributed this behavior to the coordination capability of the remaining double bond of the diene to the metallic center.…”
Section: Vanadium-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…From experimental results, it was observed that for Al/V ratios lower than 2, no reaction takes place since at least 2 alkylaluminum molecules to 1 of catalyst to form the active species is necessary. 10 For Al/V ratios between 2 and 8, we had previously observed that the yield increases until it reaches a plateau for ratio over 8, 22 probably due to an equilibrium between activation and deactivation of the catalytic species. In our proposed model, assuming that 100% of active species for Al/V corresponds to 8 and 0%, for Al/V ϭ 2, we estimated the influence of alkylaluminum on the formation of the active species (k a ).…”
Section: Initial Al/v Ratio Effectsmentioning
confidence: 92%